The target of selection matters: An established resistance—development‐time negative genetic trade‐off is not found when selecting on development time. (8th July 2020) - Bartlett, Lewis J.; Visher, Elisa; Haro, Yazmin; Roberts, Katherine E.; Boots, Mike
Abstract: Trade‐offs are fundamental to evolutionary outcomes and play a central role in eco‐evolutionary theory. They are often examined by experimentally selecting on one life‐history trait and looking for negative correlations in other traits. For example, populations of the moth Plodia interpunctella selected to resist viral infection show a life‐history cost with longer development times. However, we rarely examine whether the detection of such negative genetic correlations depends on the trait on which we select. Here, we examine a well‐characterized negative genotypic trade‐off between development time and resistance to viral infection in the moth Plodia interpunctella and test whether selection on a phenotype known to be a cost of resistance (longer development time) leads to the predicted correlated increase in resistance. If there is tight pleiotropic relationship between genes that determine development time and resistance underpinning this trade‐off, we might expect increased resistance when we select on longer development time. However, we show that selecting for longer development time in this system selects for reduced resistance when compared to selection for shorter development time. This shows how phenotypes typically characterized by a trade‐off can deviate from that trade‐off relationship, and suggests little genetic linkage between the genes governing viral resistance and those that determine response to selection on the key life‐history trait. Our results are important for both selection strategies in applied biological systems and for evolutionary modelling of host–parasite interactions. Abstract : Plodia selected for early eclosure show broadly lower susceptibility to Plodia interpunctella granulosis virus compared to Plodia selected for late eclosure. Contrast to other studies showing that selection for lower susceptibility to pathogens comes at the cost of later eclosure.